(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Osh Oblast is located in the south of Kyrgyzstan and is one of the most important regions of the country in terms of population. The study of the demographic structure of the population of Osh region helps to understand social, economic and cultural changes in the region. The article analyzes the population of Osh region, its distribution by gender and age, migration processes, trends in population placement. Population growth in the Osh region has increased significantly over the last decade, but it has also created demographic problems. Population growth affects the infrastructure, education and healthcare systems of the region, creating a number of problems in these areas. In addition, other problems related to the population, such as unemployment, the state of the agricultural sector, differences between the rural and urban population, the lack of education and medical services, all directly affect the demographic problems in the region. In the Osh region, the number of youth and able-bodied population is increasing. This demographic feature is connected with the abundance of labor force in the region, but at the same time it aggravates the problem of unemployment. Labor migration, especially the migration of the young generation to work abroad, has a negative impact on the economy and social environment of the region. Migration of the population to other regions of the country and across the border leads to the loss of labor force from the key branches of the local economy - agriculture, animal husbandry, as well as labor force. To solve the demographic problems of the region, it is necessary, first of all, to solve social issues related to population growth. For their solution, it is necessary to develop a policy aimed at expanding economic opportunities and increasing the number of jobs.